Improvement for 360˚ Marketing Communication Strategy Using Customer Relationship Management (CRM) Approach To Increase Digital Banking Platform Utilization : A Case of Kopra in PT. Bank Mandiri (Persero), Tbk - Ronald Cahaya Perdana Sihombing; Nila Armelia Windasari (Jurnal Studi Manajemen dan Bisnis, 2023)
This research aimed to understand how Customer Relationship Management is implemented through existing 360˚ marketing strategy by Bank Mandiri to promote the use of Kopra for its customers and to provide improvement for existing 360˚ marketing strategy in order to increase the utilization of Kopra on Commercial Banking customers. The methodology used for this research is quantitative and qualitative methods. The study found that the digitalization in banking industry is the new phase for banking customers to conduct their transaction. The improvement for existing 360˚ marketing communication strategy, in order to maximize utilization of “Kopra by Mandiri”, is based on CRM approach, which elaborate and dig more comprehensively toward customers situation, point of view, and possible pain points. The 3 approaches proposed to improve 3600 marketing communication strategy are educative-based marketing, customer involvement, and continuous improvement.